Charting the water regulatory future : issues, challenges and directions (New horizons in environmental and energy law, 2017)
This book is about the issues, challenges and directions currently faced by water as a key resource for mankind. The book aims at providing a finer understanding of the water regulatory future. The contributions in this book are grouped around specific themes. In Part I, the contributions address the water challenge to public international law. In Part II, the authors explore the most pressing ethical, legal, and social issues. In Part III, the discussion covers the economic drivers shaping the future of water.